2020
DOI: 10.1371/journal.pone.0228049
|View full text |Cite
|
Sign up to set email alerts
|

Unmet care needs of children with ADHD

Abstract: Background Non-compliance to, or drop-out from treatment for childhood ADHD, result in suboptimal outcome. Non-compliance and drop-out may be due to mismatches between patients' care needs and treatments provided. This study investigated unmet care needs in ADHD patients. Unmet needs were assessed in two different treatment settings (general outpatient setting versus youth-ACT). Youth-ACT treatment is an intensive outreach-oriented treatment for patients with severe psychiatric and psychosocial problems. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It is possible that young patients who break rules are less aware of their problems, or do not see the need for change [ 54 ]. Any negative experiences with adults [ 55 ]—who make and enforce rules—may also negatively affect their motivation for collaborating with treatment intended to resolve problems [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that young patients who break rules are less aware of their problems, or do not see the need for change [ 54 ]. Any negative experiences with adults [ 55 ]—who make and enforce rules—may also negatively affect their motivation for collaborating with treatment intended to resolve problems [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…A brief comparison of findings between studies scoring above/below 90% (10 studies vs. 13 studies) revealed no notable differences between groups. Sikirica et al, 2015;Simons et al, 2016;Sollie & Larsson, 2016;Vijverberg, Ferdinand, Beekman, & Van Meijel, 2020). Participants reported that medication reduces but does not eliminate ADHD symptoms (Sikirica et al, 2015;Simons et al, 2016;Sollie & Larsson, 2016) and wanted professionals to consider additional therapeutic options (Coletti et al, 2012;McIntyre & Hennessy, 2012).…”
Section: Study Selectionmentioning
confidence: 99%
“…Need: Improved access to clinical services, support and financial assistance. Though some ADHD consumers in Hong Kong reported no challenges accessing health services (Cheung et al, 2015), consumers from 14 studies (60.9%) reported gaps relating to accessing appropriate clinical services, support and financial assistance (Cheung et al, 2015;Fridman et al, 2017;Ho, Chien, & Wang, 2011;Hossainzadeh Maleki et al, 2018;McIntyre & Hennessy, 2012;Nasol et al, 2019;Pahlavanzadeh et al, 2018;Reale et al, 2015;Rezel-Potts et al, 2021;Sikirica et al, 2015;Simons et al, 2016;Spencer et al, 2021;Swift et al, 2013;Vijverberg et al, 2020). Caregivers reported challenges obtaining an ADHD diagnosis due to long waiting periods and drawn out diagnostic processes, visiting multiple doctors, problems with misdiagnosis, insufficient resources and difficulty finding professionals that would listen (McIntyre & Hennessy, 2012;Rezel-Potts et al, 2021;Sikirica et al, 2015;Simons et al, 2016).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…It is possible that young patients who break rules are less aware of their problems, or do not see the need for change [51]. Any negative experiences with adults [52] -who make and enforce rules -may also negatively affect their motivation for collaborating with treatment intended to resolve problems. [53].…”
Section: Other Signi Cant Ndingsmentioning
confidence: 99%